The high performance linpack (HPL) benchmark evaluation on UTP high performance cluster computing - Shiang, W.C. (Penerbit UTM Press, 2016)
Universiti Teknologi PETRONAS (UTP) has formed a high performance computing cluster (HPCC) inside the campus by utilizing most of the campusâ existing resources as the computing resources. All the resources are interconnected within a same network, enabling it to be accessed by users anywhere anytime within and outside the campus. The UTP HPCC is used by researchers, including lecturers and students from UTP also from external parties to compute intensive applications. However, the UTP HPCC has never been benchmarked before, hence the performance and the ability of UTP HPCC are still unverified. The benchmarking is imperative in order to measure the true performance and the ability of UTP HPCC. This paper aims to evaluate the performance of UTP HPCC using a suitable benchmarking tool as well as to determine the optimal parameters configuration of the selected benchmarking tool. A comparative study has been done in order to select the best benchmarking tool between High performance LINPACK (HPL) and the NAS Parallel. The results show that HPL is a more suitable benchmarking tool for UTP HPCC compared to NAS Parallel. A series of experiments were carried out to select the optimum parameter of HPL configuration for UTP HPCC. The results from benchmarking show that the peak performance is achievable under the test conditions. Â© 2016 Penerbit UTM Press. All rights reserved.